Política y escritura de frontera en La hija extranjera de Najat El Hachmi: la migrante como paria - Jiménez Gómez, Cristina (Studia Romanica Posnaniensia, 2020)
The autofictional novel La hija extranjera (2015), by the Catalan-Moroccan author Najat El Hachmi, is linked to the figure of exclusion and to what, in particular, Hannah Arent called “modern pariah”. Her literary writing vindicates a border thinking and the vision of a fragmentary, multiple and plural migrant female subject –contrary to the unitary male hegemonic subject – that shows, in Jacques Rancière’s terms, the close relationship that literature maintains with politics.